Dampak Dana Desa terhadap Ketimpangan Desa-Kota di Indonesia - Mudzakir, Aditya Muhammad (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2025)
This study aims to analyze whether the Village Fund (VF), which has been implemented for almost a decade since first implemented in 2015, has been able to reduce rural-urban inequality in Indonesia. Apart from being one of the national development priority agendas, reducing inequality is also one of the Sustainable Development Goals (SDGs) agendas. The research employs secondary data and consists of two main stages of analysis. First, a paired sample t-test was used to test the level of rural-urban inequality in Indonesia before (Pre) and after (Post) Village Fund. Second, the author analyzed the impact of the Village Fund on rural-urban inequality through a linear regression test. The results show that there is a decrease in rural-urban inequality by 0.0335 - 0.0462 after testing the Pre-VF and Post-VF. Meanwhile, using provincial-level panel data from 2016 to 2023, it was found that the decline of rural-urban inequality in Indonesia was affected by the Village Fund policy. It means that the Village Fund as one of the financial incentive policies for village development has an impact on rural-urban inequality reduction in Indonesia, although the impact is still extremely limited.